2020
DOI: 10.3390/ijms21030860
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Interactions of Carbapenem Antibiotics with the Multidrug Efflux Transporter AcrB of Escherichia coli

Abstract: The drug/proton antiporter AcrB, engine of the major efflux pump AcrAB(Z)-TolC of Escherichia coli and other bacteria, is characterized by its impressive ability to transport chemically diverse compounds, conferring a multi-drug resistance (MDR) phenotype. Although hundreds of small molecules are known to be AcrB substrates, only a few co-crystal structures are available to date. Computational methods have been therefore intensively employed to provide structural and dynamical fingerprints related to transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 89 publications
(161 reference statements)
0
9
0
Order By: Relevance
“…However, significant progress has been made in understanding aspects of the individual components of the overall process of drug expulsion. For example, a recent systematic study of the interaction of eight carbapenem antibiotics with the distal pocket (DP) of AcrB predicted how the physicochemical characteristics of the antibiotics may impact their binding preference [108]. In particular, Atzori et al found a correlation between the molecular weight of the carbapenems and the specific location of sub-pockets within the DP to which they preferentially bind.…”
Section: Rnd Efflux Pumpsmentioning
confidence: 99%
“…However, significant progress has been made in understanding aspects of the individual components of the overall process of drug expulsion. For example, a recent systematic study of the interaction of eight carbapenem antibiotics with the distal pocket (DP) of AcrB predicted how the physicochemical characteristics of the antibiotics may impact their binding preference [108]. In particular, Atzori et al found a correlation between the molecular weight of the carbapenems and the specific location of sub-pockets within the DP to which they preferentially bind.…”
Section: Rnd Efflux Pumpsmentioning
confidence: 99%
“…According to the sequence similarity, the efflux system can be broadly classified into five distinct families [ 42 , 47 , 168 ]. More extensive characterization work has been conducted for other species, such as P. aeruginosa [ 170 , 171 ] and E. coli [ 172 , 173 ]. Still, information is relatively sparse for Vibrio spp.…”
Section: Mechanism To Carbapenem Resistance Developmentmentioning
confidence: 99%
“…The structure of each protein forming the pump has been solved by X-ray crystallography [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ] and the whole assembly was recently determined by cryo-electron microscopy (cryo-EM) [ 13 , 14 , 15 , 16 ]. The comparison of these structures from several homologous pumps, together with in vitro measurements of transport through proteoliposomes [ 17 , 18 ], in cellulo determination of the minimal inhibitory concentration (MIC) of antibiotics for mutant strains [ 19 , 20 ], and the extensive modeling and molecular dynamic calculations [ 21 , 22 ], have led to a more precise understanding of the efflux pathways [ 23 , 24 , 25 , 26 , 27 , 28 ] and the conformational modifications [ 14 , 29 , 30 ] necessary to expulse the drugs out of the cell. We know now that the RND protein works as homotrimer with a proton motive force via proton relay amino acids localized in the membranous domain.…”
Section: Introductionmentioning
confidence: 99%